Pengaruh Brand Image, Life Style Dan Store Atmosphere Terhadap Konsumen Studi Kepuasan Di Starbuck Citadel Square Ngaliyan Semarang - oktabrian Firhannusa; Bambang Sutedjo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to analyze the influence of lifestyle, brand image, store atmosphere on consumer satisfaction for Starbuck Coffee customers at Citadel Square Ngaliyan Semarang. This type of research uses quantitative methods and the technique used in this research is non-probability sampling with purposive sampling. In addition, the data collection method was carried out using a questionnaire. In the questionnaire, the Likert scale is used to measure the value of the items in the variables. The sample used was 70 respondents. The results of the t test show that the independent variables have a partial or independent effect on customer satisfaction. In this study it is also known that the determinant coefficient (R2) is 0.859 which means 85.9%. consumer satisfaction is influenced by lifestyle, brand image, and store atmosphere variables. Meanwhile, the remaining 14.1% of consumer satisfaction is explained by variables other than lifestyle, brand image, and store atmosphere. Based on the results of this study indicate that brand image, lifestyle, store atmosphere have a positive and significant impact on consumer satisfaction. Keywords: brand image, lifestyle and store atmosphere, customer satisfaction, starbuck citadel square